Strategic positioning of white oat genotypes in the organic system - Vieira Loro, Murilo; Carvalho, Ivan Ricardo; Gonzalez da Silva, José Antonio; Alban, Aljian Antônio; Challiol, Marcio Alberto; Lautenchleger, Francine (Scientia Agraria Paranaensis, 2021)
The objective of this work was to select, under the Bayesian perspective, white oat genotypes that have high phenotypic adaptability and stability for the organic system. The study was carried out in four different environments Itapúa in Paraguay and Palotina, Candói and Três Passos in Brazil, in the 2019 crop season. The experimental design used was randomized blocks, organized in a 4x7 factorial scheme, with four environments and seven white oat genotypes (URS Taura, URS Corona, URS Brava, URS Altiva, UFPA Ouro, IPR Artemis and IPR Afrodite) arranged in 4 repetitions per environment. The following characters were evaluated: final plant population, plant height, days until flowering, days until maturation, lodging and grain yield. The use of the Bayesian method provides greater accuracy in the selection of white oat genotypes with high phenotypic adaptability and stability. The genotypes URS Brava, IPR Aphrodite and UPFA Ouro are classified as highly adaptable to unfavorable environments. The genotypes IPR Artemis, URS Corona and URS Taura exhibited high adaptability to favorable environments. The URS Brava genotype is the ideal genotype and can be placed in any environments. The characters plant height and days from emergence to flowering can be used in indirect selection for grain productivity.